The effect of email invitation elements on response rate in a web survey within an online community. (March 2016) - Petrovčič, Andraž; Petrič, Gregor; Lozar Manfreda, Katja
Abstract: In the research of online communities and web survey methodology little is known about how elements in email invitations to list-based web surveys can be used to obtain higher response rates. In the present work, we investigated whether making authority, plea for help, and sense of community salient in email invitations determines the response of survey participants. Drawing from both survey methodology and recent research on online communities, this study also tested a hypothesis on the relationship between activity in an online community and survey response. Using a full-factorial experiment based on a simple random sample of 2500 members from the largest online health community in Slovenia, the results support only the hypothesis that plea for help is an effective response-inducing element in email invitations. Furthermore, the results support the hypotheses that online community activity, related to the frequency of visits and number of posts to an online community, are positively associated with response in list-based web survey. Since this study also shows that combining more than one element in email invitations does not necessary improve response rates, web survey research and practice may benefit from future research on this topic. Highlights: We experiment with content of email invitations to web survey in online community. Authority, plea for help, and sense of community are tested as soliciting elements. Plea for help in an email invitation increases the response rate. Using more than one element does not necessary improve the response rate. Visits and posts to online community are positively related to the response rate.